Komunikat Komitetu Założycielskiego Niezależnego Samorządnego Związku Zawodowego Pracowników Uniwersytetu Wrocławskiego . no. 20, 1981 - [ed. J. Cichoń et al.] (NSZZ "Solidarność" UWr, 1981)
Creation and circulation: After introduction of the Martial Law publication suspended. Republished underground in October 1989.